Análise da proliferação de amastigotas de Leishmania (Viannia) braziliensis em macrófagos murinos - Teixeira, Mirian Vieira (2021)
Leishmania (Viannia) braziliensis is the main species responsible for American tegumentary leishmaniasis in Brazil. However, the use of this parasite species to study Leishmania infection in a murine model has been less conducted when compared to other Leishmania species. Control of murine Leishmania infection has been associated with nitric oxide (NO) produced by inducible NO synthase (iNOS) from M1 macrophage, while arginase expressed by M2 macrophages is related to Leishmania proliferation. The aim of this study was to analyze the ability of L. (V.) braziliensis to proliferate within murine macrophages in vitro for a period of 9 days. Macropha-ges were derived from bone marrow precursors (BMDM) of wild-type mice and were cultured with IFN-γ and LPS, or IL-4, or BMDM iNOS knockout (iNOS KO), and nitric oxide production, arginase activity, and infection with L. (V.) braziliensis. The number of infected macrophages and parasite load were determined by light microscopy. Promastigotes of L. (V.) braziliensis parasites were inoculated (106) into the paw of wild-type and iNOS-deficient mice and lesion progression was measured weekly. Wild-type BMDM were observed to not support proliferation of amastigotes of L. (V.) braziliensis strains after day 3 infection, even within IL-4-treated ma-crophages or iNOS KO macrophages. Arginase activity was higher in iNOS KO macrophages than in IL-4 treated macrophages, showing that the absence of proliferation is arginase inde-pendent. L. (V.) braziliensis was able to cause uncontrolled disease in iNOS KO mice in vivo. The data obtained suggest that murine macrophages do not support proliferation of L. (V.) braziliensis amastigotes, even in the absence of nitric oxide and presence of high arginase ac-tivity. Therefore, further studies related to the requirements of amastigotes internalized in host cells are needed, for the search of better methods to interfere in the diversity of leishmaniasis forms caused by different Leishmania spp.